Identifikasi Kesulitan Guru PAI dalam Pelaksanaan Penilaian Afektif di SDN Kahal Kota Cilegon - Alda Febriyanti; Al faqih Fidinillah; Anita Khusnun Niswati; Saefudin Zuhri; Wahyu Hidayat (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
Teachers not only educate and deliver content during teaching and learning activities, but they also conduct student assessments, which is a crucial component of the teacher's learning process. An affective evaluation considers behavioral traits such as attitudes, feelings, emotions, interests, and values. Affective assessment implementation has been described as tough and complicated when compared to other domain evaluations. The purpose of this study is to identify the elements that impact instructors' challenges in recognizing the application of emotional evaluations. This study employs a qualitative technique, which is a means for gathering in-depth, meaningful data. Because meaning is actual data, concrete data, and there is worth beneath the visible facts. In teaching and learning activities, teachers not only teach and provide material, but also carry out an assessment process for students, which is an important component in the teacher's learning process. The research results show that teachers as informants in this research do not fully understand the instruments and measuring tools used to carry out affective assessments in schools, which results in the emergence of various forms of difficulties felt by teachers when carrying out affective assessments.